Don't get how you do this!
I am sure you don't start working it out by multiplying the bracets but i dunno!
here it is:
5(x-3) = y(4-3x)
Thanks a bubble
You are solving for x?
$\displaystyle 5(x - 3) = y(4 - 3x)$
$\displaystyle 5x - 15 = 4y - 3xy$<-- Distribute the parentheses
$\displaystyle 5x + 3xy = 4y + 15$<-- Get all x terms on one side
$\displaystyle (5 + 3y)x = 4y + 15$<-- Factor the LHS
$\displaystyle x = \frac{4y + 15}{3y + 5}$
-Dan
what did you try?
$\displaystyle 5(x - 3) = y(4 - 3x)$ ...........expand
$\displaystyle \Rightarrow 5x - 15 = 4y - 3xy$.....now get all the terms with $\displaystyle x$'s on one side
$\displaystyle \Rightarrow 5x + 3xy = 4y + 15$
Can you take it from here?
EDIT: Oh, well, Dan finished the problem already, forget it